OVERVIEW OF FACTORS INFLUENCING DRUG MANAGEMENT AT PRIMARY HEALTH CENTERS IN INDONESIA: A SYSTEMATIC REVIEW - Khasanah, Uswatun; Yasin, Nanang Munif; Satibi, Satibi (Universitas Muhammadiyah Magelang, 2023)
Drug management is part of pharmaceutical service activities, which includes interrelated stages: selection, planning, requesting, receiving, storage, distribution, controlling, recording, reporting, monitoring and evaluation, which play an essential role in ensuring the availability of drugs at PHCs. The systematic review aims to identify indicators of drug management at PHCs in Indonesia and analyze factors that influenced it. This systematic review used the PRISMA methods. Google Scholar is an electronic database to identify related studies. This study is limited publications from 2013 to 2023. The quality of the articles was assessed using JBI Critical Appraisal. The electronics database search earned 570 articles, while only nine articles met the criteria for analysis. Several indicators are different from the standards used due to several factors. Based on the result, factors influencing drug management at PHCs include human resources, financing, information management, facilities, and technology. For most of them, human resources are a determining factor that significantly influences the quality of pharmaceutical services at PHC’s in Indonesia. The implementation of pharmaceutical services at the PHCs must be carried out by at least one pharmacist, the person in charge, who can be assisted by pharmaceutical technical staff as needed. Resources humans influence indicators of planning accuracy; suitability of requests; storage; distribution; control; recording, reporting, and archiving. This study's results are to make improvement strategies, including interventions to improve the quality of pharmaceutical services that impact community satisfaction and stakeholders.